A Forgotten Spiritual Practice: Puritan Conference and Implications for the Church Today. Issue 1 (May 2019) - Carhart, Rebecca F.
In Christian books today readers can find dozens of spiritual practices. One resource of the Protestant tradition, however, that has largely been forgotten is the Puritan practice of conference. This article describes how for the English Puritans conference exemplified the importance of communal spiritual life, then considers applications for the contemporary church. Conference refers to intentional conversation among believers about spiritual matters. Conference particularly expresses the value of Christian community and the need for the body of Christ to function together on the journey of faith. Understanding this practice not only illuminates the past but also offers valuable insights for the church today.